This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Consider f ( x ) = ( sin x − cos x ) and g ( x ) = x 3 1 . If you consider the given limit as L and the left and right hand limits of L as L l e f t and L r i g h t , then, we can see that,
L = x → 0 lim f ( x ) g ( x ) , L l e f t = x → 0 − lim f ( x ) g ( x ) , L r i g h t = x → 0 + lim f ( x ) g ( x )
Now, note that neither f ( x ) nor g ( x ) approach 0 as x → 0 + , 0 − , so we can use the product rule to separate the limits as follows:
L l e f t = ( x → 0 − lim f ( x ) ) ( x → 0 − lim g ( x ) ) , L r i g h t = ( x → 0 + lim f ( x ) ) ( x → 0 + lim g ( x ) )
Also, we have, x → 0 lim f ( x ) = x → 0 lim ( sin x − cos x ) = ( 0 − 1 ) = ( − 1 )
Now, we have a decently well known result that,
x → 0 ± lim x m 1 = { ± ∞ , when m is odd ∞ , when m is even , m ∈ Z +
In our case, g ( x ) resembles this form with m = 3 which is odd and as such, we have,
L l e f t = ( − 1 ) ⋅ ( − ∞ ) = ( + ∞ ) , L r i g h t = ( − 1 ) ⋅ ( + ∞ ) = ( − ∞ )
As we can see, L l e f t and L r i g h t neither agree nor exist finitely and as such, the two sided limit L doesn't exist.